The Development of Lightweight Clay Brick with Added Bagasse Ash - จันบัวลา, ผู้ช่วยศาสตราจารย์ ดร.สุทัศน์; วาสนาเพียรพงศ์, ผู้ช่วยศาสตราจารย์ ดร.ธรากร (Journal of Food Health and Bioenvironmental Science, 2017)
This research aimed to reuse bagasse ash waste to improve the properties of clay brick by adding 10, 20, 30, and 40 percentage of bagasse ash by weight in clay and firing at temperatures of 700, 800, 900, and 1000o C. The result showed that addition of bagasse ash resulted in increases of porosity and absorption of water, whereas it caused decreases in density, compressive strength, shrinkage and thermal conductivity. Increasing sintering temperatures resulted in decreased porosity and water absorption, however, density, compressive strength, shrinkage and thermal conductivity increased. The maximum porosity values were found with the additional 40 percent of bagasse ash sintered at 700o C. When adding 40 percent of bagasse ash, and sintering at 1000o C, brick samples had the density, compressive strength and water absorption required by Thai industrial standard of lightweight brick TIS. 2601 - 2556, with a density of 1.2 g/cm3, compressive strength of 9.42 MPa and thermal conductivity of 0.45 W/m•K and the water absorption of 21.19 %.